Reversal of Order of Information in a Multiple-Cue Probability Learning Task - Holzworth, R. James (The Journal of general psychology, 1980)
The present study investigated a modified version of the conventional paradigm employed in research on multiple-cue probability learning. The modified training paradigm, in which the criterion is presented before the cues, was compared with the conventional paradigm, in which the cues are followed by the criterion. A total of 252 male and female introductory psychology students were tested in three experiments. In Experiment I, 72 male and female Ss were required to learn the cue-criterion function form for each of three probabilistic cues. In Experiment II, 108 male and female Ss were required to learn validities of the three probabilistic cues. In Experiment III, 72 male and female Ss were required to learn cue-criterion function forms and cue validities for either three or five cues. Learning occurred with the presentation of criterion information in each experiment; however, there was no significant difference between training paradigms.